2006
DOI: 10.1021/ja064969k
|View full text |Cite
|
Sign up to set email alerts
|

Switching of Structural Order in a Cross-Linked Polymer Triggered by the Desorption/Adsorption of Guest Molecules

Abstract: A cross-linked polymer, prepared by the in situ polymerization of a thermotropic columnar liquid crystal, was found to work as a host with a flexible framework, which was reminiscent of intercalation hosts, such as clays, graphites, and coordination polymers. The structural order of the cross-linked polymer was reversibly switched by changing the amount or shape of a guest incorporated in the polymer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
49
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 11 publications
0
49
0
1
Order By: Relevance
“…There are several examples of porous materials made from LCs, however, only a few have been reported from hydrogenbonded LCs. [10][11][12][13][14][15][16][17][18][19][20][21] A class of LCs which is even less commonly investigated for its thermotropic LC properties is that of hydrogen-bonded discotic or columnar LCs. One example is of Ishida and co-workers , who demonstrate the template assisted self-assembly of columnar LCs via orthogonal ionic interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several examples of porous materials made from LCs, however, only a few have been reported from hydrogenbonded LCs. [10][11][12][13][14][15][16][17][18][19][20][21] A class of LCs which is even less commonly investigated for its thermotropic LC properties is that of hydrogen-bonded discotic or columnar LCs. One example is of Ishida and co-workers , who demonstrate the template assisted self-assembly of columnar LCs via orthogonal ionic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…One example is of Ishida and co-workers , who demonstrate the template assisted self-assembly of columnar LCs via orthogonal ionic interactions. [13][14][15] Similarly, a template-assisted approach has previously been applied to block copolymers by Gohy and co-workers and Russell and co-workers. [22][23][24][25][26][27][28][29][30][31] The current work focuses on the application of the thermotropic LC properties of columnar benzene-1,3,5-tricarboxamide (BTA) LCs for the development of porous materials, [ 32 ] in particular toward the development of porous materials with highly selective absorbing properties.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Owing to the noncovalency of the interactions between the polymer framework and the template, the resultant polymer was capable of releasing and re-capturing certain amounts of amino alcohols. Quite interestingly, the polymer showed unexpected dynamic properties, despite of its covalently cross-linked framework; [13] in response to the adsorption/desorption of the template amino alcohol; the structure of the cross-linked polymer was reversibly transformed between rectangular columnar and amorphous states (Scheme 1c and d).…”
Section: Introductionmentioning
confidence: 99%
“…[12b] 3) The structural switching mode of the polymer was limited to only one type (rectangular columnar$amorphous), unlike the case of other supramolecular hosts, such as metal-organic frameworks. [13] Therefore, we newly employed three kinds polymerizable carboxylic acids as the matrix unit and systematically varied the polymerizable (Scheme 1, M DDD , M ANA , and M DND ). Here we report a detailed study on the properties of the resultant polymers, which revealed that the modification of the polymerizable parts had an unexpectedly large effect on their performance as solid-state hosts.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, click chemistry, [2] diene metathesis, [3] and disulfide bond formation [4] have been successfully utilized to stabilize various structures such as gel fibers, self-assembled nanotubes, and host frameworks. [5] Subtle control of the reaction conditions is required to maintain the structure and morphology and to simultaneously achieve efficient covalent cross-linking, which are the key factors that determine the final performance of the supramolecular materials in practical applications.…”
mentioning
confidence: 99%